Comparison of Neural Response Telemetry and Electrical Stapedius Reflexes with Behavioral Thresholds in Cochlear Implant Users - Bayat, Arash (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The present study aimed to compare neural response telemetry (NRT) and electrical stapedius reflex (ESR) with behavioral thresholds in pre- and post-lingual cochlear implant (CI) recipients. Materials and Methods: A total of 30 patients (15 males and 15 females) aged 3–40 years old were participated in this study. They were underwent CI operation at Khuzestan CI, Ahvaz, Iran, from March 2013 to August 2016. The NRT and ESR values were measured in all patients and compared with the respective behavioral threshold at the same time. Results: The NRT and ESR thresholds were determined successfully in all patients. The NRT thresholds showed significant correlation with the C-levels (r = 0.645, P < 0.001) and fell at 74.12% of the dynamic range of the map in children and at 85% in adults. Our data indicated that there was a strong correlation between the mean ESR and behavioral thresholds (C-levels) in children (r = 0.78, P = 0.004) and adults (r = 0.82, P < 0.001). The mean behavioral thresholds were identical between males and females (independent sample t-test, P > 0.05). In addition, both NRT and ESR showed no statistical difference between males and females (independent sample t-test, P > 0.05). Conclusion: Both ESR and NRT thresholds showed strong correlation with the respective behavioral thresholds; however, the ESR threshold may be a better predictor of C-levels values compared with the NRT thresholds.